Transposon mutagenesis screen in mice identifies TM9SF2 as a novel colorectal cancer oncogene. Issue 1 (December 2018) - Clark, Christopher; Maile, Makayla; Blaney, Patrick; Hellweg, Stefano; Strauss, Anna; Durose, Wilaiwan; Priya, Sambhawa; Habicht, Juri; Burns, Michael; Blekhman, Ran; Abrahante, Juan; Starr, Timothy
Abstract New therapeutic targets for advanced colorectal cancer (CRC) are critically needed. Our laboratory recently performed an insertional mutagenesis screen in mice to identify novel CRC driver genes and, thus, potential drug targets. Here, we defineTransmembrane 9 Superfamily 2 (TM9SF2 ) as a novel CRC oncogene. TM9SF2 is an understudied protein, belonging to a well conserved protein family characterized by their nine putative transmembrane domains. Based on our transposon screen we found thatTM9SF2 is a candidate progression driver in digestive tract tumors. Analysis of The Cancer Genome Atlas (TCGA) data revealed that approximately 35% of CRC patients have elevated levels ofTM9SF2 mRNA, data we validated using an independent set of CRC samples. RNAi silencing of TM9SF2 reduced CRC cell growth in an anchorage-independent manner, a hallmark of cancer. Furthermore, CRISPR/Cas9 knockout ofTM9SF2 substantially diminished CRC tumor fitnessin vitro andin vivo . Transcriptome analysis ofTM9SF2 knockout cells revealed a potential role for TM9SF2 in cell cycle progression, oxidative phosphorylation, and ceramide signaling. Lastly, we report that increasedTM9SF2 expression correlates with disease stage and lowTM9SF2 expression correlate with a more favorable relapse-free survival. Taken together, this study provides evidence thatTM9SF2 is a novel CRC oncogene.